Investigation of Tourist Satisfaction with the Public Transporation in Bali - Putu Ayu Aryasih; Dessy Ruhati; Ida Bagus Putu Puja; Made Darmiati; I Wayan Widiana; Putu Ferry Krisna Mahendra (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2024)
Bali, a popular tourist destination in Indonesia, faces challenges from mass tourism, including ecological degradation and cultural changes. This study aims to examine Bali's transportation system using a mixed-method approach. Qualitative data from field observations and interviews were combined with quantitative data on transportation quality. Qualitative findings highlighted issues such as traffic congestion, while quantitative data revealed specific numbers on passenger satisfaction levels. Integrating both methods provided a comprehensive understanding of Bali's transportation landscape. The study emphasizes the role of technology in improving public transit services and enhancing tourist experiences. The implications include the importance of sustainable tourism planning and infrastructure development in addressing transportation issues in Bali.